2017
DOI: 10.4314/ejesm.v9i2.3s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of train speed performance on Nigeria railway corporation Lagos district narrow gauge track

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Synthetic track quality coefficient and speed limits at rail station It should be noted that the permissible speeds over any section of the rail track are calculated on the basis of safety and passenger comfort but for operational purpose the achievable speed is more advisable Dina and Raji (2016). observed that average speed of 40 km/h with maximum speed of about 53 km/h and minimum speed of 20km/h are common within Lagos district narrow gauge track.…”
mentioning
confidence: 99%
“…Synthetic track quality coefficient and speed limits at rail station It should be noted that the permissible speeds over any section of the rail track are calculated on the basis of safety and passenger comfort but for operational purpose the achievable speed is more advisable Dina and Raji (2016). observed that average speed of 40 km/h with maximum speed of about 53 km/h and minimum speed of 20km/h are common within Lagos district narrow gauge track.…”
mentioning
confidence: 99%